Analisis peran media sosial dalam meningkatkan tingkat hunian kamar the jayakarta bali beach resort residence and spa - Pradana, Ricky Julio; Suarka, Fanny Maharani; Ariana, I Nyoman Jamin (Jurnal Kepariwisataan dan Hospitalitas; Vol 8 No 2 (2024): Vol.8,No.2,2024, 2024)
The decline in tourism industry activities causes hotel management to have to twist its brains to increase the existence and financial losses experienced during the pandemic of the impact of Covid19 because if we do not have more value that can attract guests, then the hotel will be left behind in the competition The role of social media serves as a place in promoting a product coupled with the Covid-19 pandemic. The purpose of this research is the role of social media in sales and marketing in increasing the occupancy rate of The Jayakarta Bali Beach Resort Residence And Spa and To find out the perception of hotel guests The Jayakarta Bali Beach Resort Residence And Spa towards promotion on social media This study was conducted at The Jayakarta Bali Beach Resort Residence And Spa with respondents numbering 50 respondents, The samples in this study used Purposive sampling with data collection techniques through observations, interviews and questionnaires. Qualitative descriptive analysis technique using the likert scale using the slovin formula, the way the measurement is by facing respondents to a question and asked to provide answers with excellent attitude categories, good, sufficient, less, and very lacking. Answer – this answer is given a score of 1 for the lowest and a score of 5 for the highest. Based on the results in the discussion that has been spelled out in each of the previous chapters and in accordance with the analysis of the role of social media that can be applied to The Jayakarta Bali Beach Resort And Spa. Based on the results of the study, it can be concluded that the role of social media to Sales and Marketing at The Jayakarta Bali Beach Resort Residence And Spa based on the results of interviews effectively helps Sales and Marketing in increasing room occupancy rates. The perception of guests who have stayed at the role of social media at The Jayakarta Bali Beach Resort And Spa is with an average of 4.10 which means it has a good interval so that the analysis of the role of social media in The Jayakarta Bali Beach Resort And Spa and Resort And Spa is optimal in increasing room occupancy. The most dominant social media promotion in increasing room occupancy rates at The Jayakarta Bali Beach Resort Residence And Spa hotel is instagram social media in conclusion is the social media promotion of The Jayakarta Bali Beach Resort And Spa optimal in increasing room occupancy. Keywords: Role analysis, social media, sales and marketing, room occupancy, Hotel